The relationship between sleep duration and health status in Qatar's population - Maryam A. Al-Thani; Salma M. Khaled, PhD (Elsevier, 2020)
Knowledge of sleep duration correlates is limited to developed countries with a lack of studies in the Eastern Mediterranean Region (EMR). Qatar is a rapidly developing country in the EMR with three distinct population groups: Qatari nationals (QNs) or natives; higher income white-collar expatriates (WCEs), and blue-collar workers (BCEs) who are mostly male laborers from South Asia. The aim of this study was to explore the association between sleep duration, chronic health conditions, important lifestyle variables, and sociodemographic characteristics in a representative sample of Qatar's general population. A total of 2523 surveys were administered over the phone and a final sample of 2500 was retained. The overall prevalence of sleeping < 7hrs was observed at 54%, while 42% of respondents reported sleeping 7-8hrs and 4% reported sleeping > 8hrs. Qatar's population exhibited low prevalence of normal sleep duration and high prevalence of short sleep duration. Participants who reported the poorest health status had increased odds of sleeping < 7hrs (OR 1.38, P ​= ​0.04) compared with those who reported good health after adjustment for covariates. Additionally, participants with two or more diagnosed illnesses had higher odds of sleeping < 7hrs (OR 1.58, P ​= ​0.02) compared to healthy participants. An increase in odds of sleeping < 7hrs was also observed in participants with obesity (OR 1.58, P ​= ​0.02). Qatar's population exhibited high prevalence of short sleep duration, which was significantly associated with poor rated health, obesity, and chronic illness independent of age, gender, or social class.